Comparative analysis for oral health status of old age home residents and its association with depression in Eastern Nepal - Ujwal Gautam; Ashish Shrestha; Tarakant Bhagat; Dharanidhar Baral; Suraj Nepal (Journal of Karnali Academy of Health Sciences, 2025)
Background: Changing family practice has led to increased number of ageing population in old age homes. Multiple factors have a role in deteriorating oral health of older adults. The study assesses and compares oral health status in old-age home residents of eastern Nepal with community dwelling counterparts and look into its association with depression.  Methods: A cross-sectional study was conducted among 42 older adults from old age homes and community each. Old age home residents were selected using multistage random sampling while community dwelling older adults were selected using systematic random sampling after matching for age and sex. Structured questionnaires were used to interview participants on oral health behaviour and depression. Oral examination was conducted to assess plaque control, caries outcome and periodontal status. Oral health outcomes were compared across two population using inferential statistics like chi-square test, or Mann Whitney U test. Logistic regression was conducted to explore how oral health outcome variables were influenced by depression and other covariates.